2013
DOI: 10.5455/vetworld.2013.106-108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol, vitamin A, E and selenium treatment with varying sexual rest period on recovery rate in cross-bred cows with chronic endometritis

Abstract: Aim:This work was done to study the effect of vitamin A, E and Se with varying sexual rest period in cross-bred cows with chronic endometritis. Materials and Methods: Cross-bred cows (n=396) from different villages of West Bengal with purulent or muco-purulent discharge with a history of infertility and repeat breeding for 3 to 6 months were chosen for the present study. These cows received uterine wash with lugol's iodine, intra-uterine and parenteral antibiotics and de-worming as general treatment. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Our findings may be due to synergistic effect of systemic and intrauterine antibiotics with oestradiol by stimulation of endometrial blood flow and increasing uterine leukocytic response [32]. This result agrees with Sengupta D and Nandi PR [33]. …”
Section: Resultssupporting
confidence: 82%
“…Our findings may be due to synergistic effect of systemic and intrauterine antibiotics with oestradiol by stimulation of endometrial blood flow and increasing uterine leukocytic response [32]. This result agrees with Sengupta D and Nandi PR [33]. …”
Section: Resultssupporting
confidence: 82%
“…The effect of reduction of post-coital endometritis performed by equine seminal plasma has already been demonstrated (Troedsson et al 2001), and OS has been proposed as a potential factor involved in the pathogenesis of the endometritis in mares (Yaralioglu-Gurgoze et al 2005). Some authors demonstrated that intramuscular treatments with antioxidants increase the recovery rate in chronic endometritis in cows (Segupta & Nandi 2013). Its effect in the uterus may explain its presence in seminal plasma, as it does not seem to give any improvement directly in the spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium is a unique pro-oxidant and antioxidant trace element that minimizing cellular damage by improving the efficiency of the cell antioxidant system (Durmus et al, 2011 andSengupta andNandi, 2013). Selenium was found to stimulate uterine defense mechanism (Thatcher et al, 2011), by improving neutrophil functions (Cebra et al, 2003), and general uterine health (Cerri et al, 2009), by supporting uterine tissue remodeling and involution (Rao et al, 2016) through its effect on the uterine motility (Segerson et al, 1980); so, decreasing metritis rate (Harrison et al, 1986), and increasing the rate of endometritis recovery if used synergistically with vitamin E (Sengupta and Nandi, 2013).…”
mentioning
confidence: 99%